Violencias literarias. Mecanismos de exclusión ejercidos contra las escritoras de Morelia y propuestas para desactivarlos - Rojas Iglesias, Nektli Necuhtli (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
This work, developed under the precepts of literary feminist critique, analyses and a reflects upon the violence exercised against women writers in Morelia. It uses the gender methodology (Golubov, Harding, Comesaña) and life stories methodology (based in Anabel Moriña) to collect the experiences of fourteen women writers of Morelia so that their stories can be made visible. This experiences are categorized with a tool based in the work of Joanna Russ (How to Suppress Women’s Writing) and Buquet, Mingo, Cooper and Moreno (Intrusas en la universidad, Intruders in the University). We consider these violences as a mechanism to create exclusion that the sworn literary group (groupe juré) exercises, denomination that comes from the theoretical contributions of Adriana Sáenz, with which it creates epistemic injustice (proposed by Fricker) that excludes women writers from contributing to the literary tradition. The violence is classified in psychological violence, violence related to the literary exercise and sexual harassment. In the first type, we recognize informal prohibitions, obstacles in training, undermining and self-directed literary violence. In the latter, questioning authorship and misrepresentation both of the written work and the author. Conjoining with feminist methodology, in this investigation we propose some ways to deactivate this violence proposed by the authors themselves as well as by cultural managers. These are framed in Fraser’s levels of redistribution, recognition, and representation.

El presente trabajo, que se inserta en los estudios de crítica literaria feminista, hace un análisis y una reflexión sobre las violencias que se ejercen en contra de las escritoras de Morelia. Se hace uso de la metodología de género (Golubov, Harding, Comesaña) y los relatos de vida (retomados de Anabel Moriña) para recabar las experiencias de catorce escritoras de Morelia, de modo que sus experiencias puedan ser visibilizadas. Éstas se clasifican con una herramienta basada en los trabajos de Joanna Russ (How to Suppress Women’s Writing) y Buquet, Mingo, Cooper y Moreno (Intrusas en la universidad). Se considera a estas violencias como mecanismos que generan exclusión y que son aplicados por el grupo juramentado literario, al que se nomina así con base en las aportaciones teóricas de la Dra. Adriana Sáenz, con lo que se ocasiona una injusticia epistémica (concepto retomado de Fricker) que excluye a las escritoras de contribuir al acervo literario. Las violencias se clasifican en violencias psicológicas, del ejercicio literario y acoso sexual. En las primeras, se reconocen prohibiciones informales, impedimentos a la formación, menoscabo y autoviolencia literaria; en las segundas, cuestionamiento de la autoría, representación tergiversada tanto de la obra escrita como de la autora. En conjunción con la metodología feminista, en la investigación se proponen algunas maneras de desactivar estas violencias, provenientes tanto de las propias escritoras como de gestores culturales, y se enmarcan en los niveles de redistribución, reconocimiento y representación de la propuesta de justicia de Nancy Fraser.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2021-1411; Feminismo; Literatura; Injusticia epistémica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6514